2013
DOI: 10.1371/journal.pone.0065075
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Invariant Natural Killer T Cells in the 5T33 Multiple Myeloma Model

Abstract: Immunomodulators have been used in recent years to reactivate host anti-tumor immunity in several hematological malignancies. This report describes the effect of activating natural killer T (NKT) cells by α-Galactosylceramide (α-GalCer) in the 5T33MM model of multiple myeloma (MM). NKT cells are T lymphocytes, co-expressing T and NK receptors, while invariant NKT cells (iNKTs) also express a unique semi-invariant TCR α-chain. We followed iNKT numbers during the development of the disease in both 5T33MM mice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
5
28
1
2
Order By: Relevance
“…Engagement of CD1d (NKT ligand) also kills tumour cells in vitro [21], and NKT cells specific for an inflammationassociated lipid antigen, lysophosphatidylcholine, have been detected in patients with advanced myeloma [22]. Collectively, these findings indicate why a defective NKT cell pool may be associated with MM onset and relapse and support the concept that therapeutic targeting of NKT cells may be a useful strategy in treatment of MM in humans [12,13,16,17,19,23].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Engagement of CD1d (NKT ligand) also kills tumour cells in vitro [21], and NKT cells specific for an inflammationassociated lipid antigen, lysophosphatidylcholine, have been detected in patients with advanced myeloma [22]. Collectively, these findings indicate why a defective NKT cell pool may be associated with MM onset and relapse and support the concept that therapeutic targeting of NKT cells may be a useful strategy in treatment of MM in humans [12,13,16,17,19,23].…”
Section: Introductionmentioning
confidence: 68%
“…Earlier reports had indicated that NKT cell defects may be important in the development of MM [8,12,13,17,18] and that NKT cells could be a new target for immune-based treatment of MM patients [20,23]. To investigate the therapeutic significance of NKT cells in MM, we analysed NKT cell frequency and function in longitudinal studies of newly diagnosed patients with MM throughout several stages of therapy, with an emphasis on identifying and defining any NKT cell defects and determining the impact of lenalidomide treatment on NKT cell frequency and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agents include MK3475 (Pembrozilumab, Keytruda, by Merck & Co's) with pomalodomide (NCT02289222), with Len/Dex (NCT02036502), or post ASCT (NCT02331368), and the BMS-936558 (nivolumab, Bristol-Myers Squibb) NCT01592370 with other checkpoint inhibitors. (Qian et al, 2012;Freeman et al, 2011;Barber et al, 2011;Hofgaard et al, 2012;Nur et al, 2013 …”
Section: Pd-1/pd-l1mentioning
confidence: 99%
“…71,72 The monoclonal antibodies FRMF7 (elotuzumab) 42 and anti-CD38 (daratumumab, SAR650984), 66,73 particularly when associated with bortezomib/dexamethasone or lenalidomide/dexamethasone, may result in a relevant improvement. A newer exciting approach is immunotherapy with modified virus use, 74 natural killer cell therapy, 75,76 or chimeric antigen receptor strategies, 77 combining activity against malignant plasma cells and T-cell receptors. The above and other potential effective drugs in MM [78][79][80][81][82][83][84][85][86] are listed in Table 3.…”
Section: Future Directionsmentioning
confidence: 99%